DETERMINANT FACTORS COUPLES TO AVOID HAVING MORE CHILDREN IN BALI PROVINCE - Putu Ayu Indrayathi; Istiana Marfianti; Putu Erma Pradnyani; Luh Putu Sinthya Ulandari; Anastasia Septya Titisari; Luh Kadek Ratih Swandewi (Universitas Airlangga, 2022)
The number of married women and men who no longer want children in Bali Province is consistent with a relatively high contraceptive prevalence rate (CPR) of 67%, higher than the national average of 64%. The large proportion of couples of reproductive age (CRA) who no longer want children either at the national or provincial level in Bali is an interesting thing to be analyzed further to see the factors that influence it. This study investigated secondary data of the 2017 Indonesia Demography and Health Survey (IDHS) in Bali Province. The variables studied included socio-demographics and desire to have children. The sample size was 271 married women (15-49 years). We found that the age of women of reproductive age (WRA), occupation of WRA, number of children alive, and ideal number of children are the four significant factors that influence the desire to have no more children in married couples. Based on these findings, a better family planning program can hopefully be made in the Bali province.